High drug prices are not justified by industry's spending on research and development. (15th February 2023) - Angelis, Aris; Polyakov, Roman; Wouters, Olivier J; Torreele, Els; McKee, Martin
Abstract : Aris Angelis and colleagues argue that by refocusing their spending drug companies could provide more innovative drugs at affordable prices